2010
DOI: 10.1016/j.yebeh.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor attenuates status epilepticus-induced behavioral impairments in rats

Abstract: Vascular endothelial growth factor (VEGF) is a vascular growth factor more recently recognized as a neurotrophic factor (for review see 1). We previously reported that endogenous VEGF protein is dramatically upregulated after pilocarpine-induced status epilepticus in the rat, and that intra-hippocampal infusions of recombinant human VEGF significantly protected against the loss of hippocampal CA1 neurons in this model2. We hypothesized that we would see a preservation of cognitive and emotional functioning wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Neuronal and glial cells regulate the VEGF expression after seizures in the rodent hippocampus, suggesting a neuroprotective role of VEGF in epilepsy . Besides, VEGF has also been found to significantly protect learning and memory after SE . Our findings that epileptic tissues promote a significant increase in VEGF production in response to BMMCs suggest that this mechanism could contribute to the cognitive preservation we observed in previous studies using BMMC transplantation in epilepsy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Neuronal and glial cells regulate the VEGF expression after seizures in the rodent hippocampus, suggesting a neuroprotective role of VEGF in epilepsy . Besides, VEGF has also been found to significantly protect learning and memory after SE . Our findings that epileptic tissues promote a significant increase in VEGF production in response to BMMCs suggest that this mechanism could contribute to the cognitive preservation we observed in previous studies using BMMC transplantation in epilepsy.…”
Section: Discussionsupporting
confidence: 70%
“…A large array of growth factors has control upon cell survival, proliferation, and differentiation in the central nervous system . In our study, we focused on BDNF, NGF, GDNF, VEGF, and TGF‐ β 1 because several reports in the literature suggest that these factors are involved in epileptogenic processes . Here, we showed that BDNF protein was increased 14 days posttransplantation, and BDNF mRNA and TrkB mRNA receptor expressions were increased 7 days posttransplantation in relation to saline‐treated epileptic animals.…”
Section: Discussionmentioning
confidence: 78%
“…The relationship between adult neurogenesis and the NVU has been studied (Goldman and Chen, 2011), and a recent study reported that microvascular hemodynamics modulate adult neurogenesis (Shen et al, 2019). Furthermore, VEGF administration suppressed neuronal loss in the hippocampal CA1 region 24 h but not one month after pilocarpine-induced SE in rats (Nicoletti et al, 2010). Additionally, when rats were treated with VEGF and angiopoietin-1, VEGF-induced vascular permeability was suppressed without affecting neuroprotective effects of VEGF (Nicoletti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has also been recognized as a neurotrophic factor [27,28], which could potentially protect vulnerable cells from seizures related damage [26]. VEGF induced significant preservation of hippocampal neurons after SE [4], completely preserved normal anxiety functioning, and partially but significantly protected learning and memory in the rat after pilocarpine-induced SE [29].…”
Section: Discussionmentioning
confidence: 99%